Cinobufotalin effect and mechanism on serum MMP-2, MMP-9, Beclin1, LC3-II in advanced NSCLC patients: Effect of cinobufotalin on patients with advanced NSCLC - Yang, Lei; Bai, Bihui; Chen, Hongyu; Li, Tielian; Wang, Mingting; Zhu, Xuedong (Cellular and Molecular Biology, 2023)
This study was conducted to explore cinobufotalin’s effects and related mechanisms on serum MMP-2, MMP-9, Beclin1, and LC3-II in advanced non-small-cell lung cancer (NSCLC) patients. For this purpose, 150 patients with advanced NSCLC in our hospital from Jan. 2020 to Feb. 2022 were chosen as participants in the research study. Using a random number table method, the 150 patients were divided evenly into two groups - a control group (C) and an observation group (O). Group C received conventional NP regimen chemotherapy, while Group O received cinobufotalin capsules based on the control group. The follow-up was conducted for 4 months, and the differences in serum MMP-2, MMP-9, Beclin1, LC3-II and chemotherapy resistance rates were compared. Results showed that There was no statistically significant difference in MMP-2, MMP-9, Beclin1, and LC3-II levels between the two before treatment (P>0.05); 4 months later, Group O’s MMP-2, MMP-9, Beclin1, and LC3-II levels were lower than those before treatment and Group C during the same period, with a statistically significant difference (P<0.05); At 4 months after treatment, the clinical efficacy of Group O was better and its ORR was higher, with a statistically significant difference (P<0.05); Using Pearson correlation analysis, a weak positive correlation was identified between MMP-2, Beclin1, LC3-II, and chemotherapy resistance (r=0.167, 0.197, 0.273, P<0.05), a positive correlation between MMP-2 and MMP-9, Beclin1, LC3-II (r=0.592, 0.852, 0.665, P<0.01), a positive correlation between MMP-9 and Beclin1, LC3-II (r=0.552, 0.472, P<0.01), and a positive correlation between Beclin1 and LC3-II (r=0.647, P<0.01). It was concluded that cinobufotalin has an inhibitory effect on the serum MMP-2, MMP-9, Beclin1, and LC3-II levels in advanced NSCLC patients, which can promote clinical efficacy improvement and reduce the risk of chemotherapy resistance by downregulating MMP-2, Beclin1, and LC3-II levels.